Park access and mental health among parents and children during the COVID-19 pandemic - Marnie F. Hazlehurst; Sadiya Muqueeth; Kathleen L. Wolf; Cary Simmons; Emily Kroshus; Pooja S. Tandon (BMC, 2022)
Abstract Background Time spent outdoors and in nature has been associated with numerous benefits to health and well-being. We examined relationships between park access and mental health for children and parents during the COVID-19 pandemic. We also explored associations between park access and co-participation of parent and child in time outdoors, and child and parent physical activity. Methods We used data from 1,000 respondents to a nationally representative U.S. survey of parent-child dyads during October-November 2020. Park access was defined as an affirmative response to: "do you have a park that you can safely walk to within 10 min of your home?" Child mental health was operationalized as the Strengths and Difficulties Questionnaire (SDQ) total difficulties score. The Patient Health Questionnaire-4 (PHQ-4) total score assessed parent mental health and the International Physical Activity Questionnaire (IPAQ) assessed parent physical activity. Child physical activity and co-participation in outdoor activity were reported as number of days in the prior week. Linear regression was used to examine relationships between park access and health outcomes in models adjusted for child and parent characteristics and COVID-19 impact. Results Our sample included 500 parents of children ages 6-10 years, and 500 parent-child dyads of children ages 11-17 years. Park access was associated with a lower SDQ total score among children (β: -1.26, 95% CI: -2.25, -0.27) and a lower PHQ-4 total score among parents (β: -0.89, 95% CI: -1.39, -0.40). In models stratified by child age, these associations were observed for SDQ scores among adolescents ages 11-17 and for PHQ-4 scores among parents of children ages 6-10 years. Park access was also associated with 0.50 more days/week of co-participation in outdoor time (95% CI: 0.16, 0.84), and higher levels of parent physical activity (β: 1009 MET-min/week, 95% CI: 301, 1717), but not child physical activity (β: 0.31 days/week, 95% CI: -0.03, 0.66). Conclusions Park access was associated with better mental health among children and parents, and more parent physical activity and parent-child co-participation in outdooractivity during the COVID-19 pandemic. Access to nearby parks may be an important resource to promote health and well-being, for both individuals and families.